2011
DOI: 10.7589/0090-3558-47.3.690
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Human Herpesvirus Type 1 Infection in Nonhuman Primates (Callithrix penincillata)

Abstract: ABSTRACT:Human herpesvirus type 1 (HHV-1) is widely dispersed among the human population. Although infection is often asymptomatic in humans, nonhuman primates develop a severe and often fatal infection. In August 2006, 13 black-tufted marmosets (Callithrix penincillata) from a group of 14 presented with clinical apathy, anorexia, and ataxia. Physical examination revealed conjunctivitis, erosive or ulcerative lesions on the skin, and swollen lymph nodes. Of the 14 animals captured, 10 died. Grossly, ulcers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 11 publications
7
21
0
Order By: Relevance
“…This profile has also been reported in other studies related to HSV-1, in P. pithecia and in C. jacchus [36,39]. The histopathological findings that we visualize in the brains of the animals corroborate with those of other reports regarding the presence of gliosis, neuroniophagia, eosinophilic inclusion corpuscle, monolymphocytic meningitis and dilated and congested blood vessels [4,11,16,17,20,21,[35][36][37][38][39]42]. We observed that the kidneys of the monkeys presented areas of necrosis, marked tubulonefrosis and ballooning degeneration with hyaline material, interstitial hemorrhage with increased Bowman space.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This profile has also been reported in other studies related to HSV-1, in P. pithecia and in C. jacchus [36,39]. The histopathological findings that we visualize in the brains of the animals corroborate with those of other reports regarding the presence of gliosis, neuroniophagia, eosinophilic inclusion corpuscle, monolymphocytic meningitis and dilated and congested blood vessels [4,11,16,17,20,21,[35][36][37][38][39]42]. We observed that the kidneys of the monkeys presented areas of necrosis, marked tubulonefrosis and ballooning degeneration with hyaline material, interstitial hemorrhage with increased Bowman space.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that the kidneys of the monkeys presented areas of necrosis, marked tubulonefrosis and ballooning degeneration with hyaline material, interstitial hemorrhage with increased Bowman space. The kidneys of the A. trivirgatus, C. peniciliata and the A. nancymae, também showed signs of necrosis and inflammation [14,21,39]. Casagrande et al found multinucleated syncytial cells in the kidneys of C. jacchus and C. penicillata [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address some of these issues, smaller primates, such as common marmosets (Callithrix jacchus), are considered more suitable as a NHP model for SCI with relatively smaller body size (length 20-35 cm; weight 200-600 g), shorter developmental period (18 months), better reproductive output (1-2 offspring), and shorter interbirth intervals (6 months; see Table 1) [22]. However, both M. fascicularis and C. jacchus carry and can transmit serious zoonotic diseases, including hepatitis B [23], herpes virus [24,25], and tuberculosis [26,27]. Furthermore, high maintenance costs can limit their widespread application as animal models for central nervous system trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with active infection exhibit oral ulcers and gingivitis, which usually transit to latent infection in the nervous system with no or intermittent manifestation and virus production. Herpes simplex virus type 1 infection has been reported in apes, such as orangutan ( Pongo pygmaeus ) [ 13 ], gorilla ( Gorilla gorilla ) [ 9 ] and white-handed gibbon ( Hylobates lar ) [ 6 , 14 ], and new world monkeys, such as common marmoset ( Callithrix jacchus ) [ 10 , 12 ], black-tufted marmoset ( Callithrix penicillata ) [ 3 , 5 ], night monkey ( Aotus trivirgatus ) [ 16 ] and white-faced saki ( Pithecia pithecia pithecia ) [ 17 ].…”
mentioning
confidence: 99%